ANALISIS PERTANGGUNGJAWABAN ALOKASI DANA DESA (ADD) STUDI PADA DESA LAM ARA DI KECAMATAN BANDA RAYA KOTA BANDA ACEH - Agusthian, Ananda; Muniruddin, Said (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
The purpose of the research is to describe and analyze accountability village funds allocation in Lam Ara Village. The method used is data analysis with a descriptive qualitative approach. Data collection was taken by interviewing several employees working in the Lam Ara Village Office in Banda Aceh. The results of the study show that The accountability phase of the Village Fund Allocation (ADD) in Lam Ara, both technically and administratively is good, but must still receive guidance from the Banda Aceh City government, Implementation of the use of village funds has applied the principle of accountability. Thus it is necessary to make improvements on an ongoing basis while still adjusting the situation and conditions and the development of applicable laws and regulations